Comparison of Dexmedetomidine with Acetaminophen and Its Combination (Apodex) on Pain Control, Emergence Agitation and Delirium in Pediatric Patients Undergoing Adenotonsillectomy with Sevoflurane - farzad sarshivi; negin ghadami; karim naseri; soraya sarshivi (مجله علمی دانشگاه علوم پزشکی کردستان)
Background and Aim: Adenotonsillectomy is one of the most common pediatric surgeries and is often associated with postoperative emergence agitation and pain. The aim of this study was to comparison of dexmedetomidine with acetaminophen and its combination (Apodex) on pain control, emergence agitation and delirium in pediatric patients undergoing adenotonsillectomy with sevoflurane. Materials and Methods: In this randomized double-blind clinical trial, 132 patients, between 2 and 12 years, candidates for adenotonsillectomy were examined in four groups (n=33). In all groups induction of anesthesia were performed in a similar manner. In the first group, acetaminophen (15 mg/kg), in the second group, dexmedetomidine (1 µg/kg), in the third group, apodex, which is a combination of acetaminophen (10 mg/kg) and dexmedetomidine (0.3 g/kg) were prescribed. The fourth group received (50 ml) normal saline as a placebo intravenously within 15 minutes before the end of surgery. Version 12 of STATA software was used for data analysis. Results: Acetaminophen, dexmedetomidine and apodex reduced pain, emergence agitation and delirium compared with the control group (P<0.05). It should be noted that dexmedetomidine and apodex had better effects compared with acetaminophen (P<0.05). Conclusion: Acetaminophen, dexmedetomidine and apodex can be used to control pain, emergence agitation and delirium after adenotonsillectomy. Dexmedetomidine and apodex have better effects in controlling pain and emergence agitation.